Why don't health care frontline professionals do more for segregated Roma? Exploring mechanisms supporting unequal care practices - Belak, Andrej; Filakovska Bobakova, Daniela; Madarasova Geckova, Andrea; van Dijk, Jitse P; Reijneveld, Sijmen A (Social science & medicine (1982), 2020)
RATIONALE: Unequal provision of health care contributes to the poor health status of segregated Roma in Central and Eastern Europe. Studies on the drivers and mechanisms behind this are lacking. OBJECTIVE: We explored what kinds of substandard practices health care frontline professionals engage in regarding segregated Roma and what mechanisms support such practices during the professionals' careers in care services. METHODS: Over a three-month period at five different locations in Slovakia we interviewed and observed 43 frontline professionals serving segregated Roma. Next, through qualitative content analysis we identified in the data three themes regarding kinds of substandard practices and 22 themes regarding supporting mechanisms. We organized these themes into an explanatory framework, drawing on psychological models of discrimination and intergroup contact. RESULTS: The frontline staff's substandard practices mostly involved substandard communication and commitment to care, but also some overt ethnic discrimination. These practices were supported by five mechanisms: the staff's negative experiences with people labelled "problematic Roma patients"; the staff's negative attitudes regarding segregated Roma; adverse organizational aspects; adverse residential-segregation aspects; and poor state governance regarding racism. In the course of their careers, many professionals first felt obliged and diligent regarding segregated Roma patients, then failing, unequipped and abandoned, and ultimately frustrated and resigned regarding the equal standard of care towards the group. CONCLUSIONS: Health care frontline staff's practices towards segregated Roma are frequently substandard. The psychological processes underlying this substandard care are supported by specific personal, organizational and governance features. These mechanisms cause many frontline professionals gradually to become cynical regarding segregated Roma over the course of their careers. Health care staff should be supported with skills and tools for effectively handling their own and others' racism, the culturebound and structural vulnerabilities of patients as well as related professional expectations regarding equity.
Keywords: Romové; poskytování zdravotní péče; Humans; Slovakia; Delivery of Health Care; Roma health; Health inequalities; Qualitative research; Slovenská republika; Ethnography; Health services; Social Segregation; sociální segregace; lidé; východní Evropa; Racism; Roma; Discrimination; Europe, Eastern